PENERAPAN GREEN ACCOUNTING PADA LAPORAN KEUANGAN UMKM (STUDI LITERATUR PADA UMKM DI INDONESIA) - Ineldis Narsi; Anita Bessi; Beatrix Yunarti Manehat (JAKA - Jurnal Jurusan Akuntasi, 2023)
The purpose of this study was to see how green accounting is applied to the financial statements of MSMEs in Indonesia. This research uses the library search method. This method directs researchers to search, find and analyze data from journals, books and various other literature related to the research topic. MSMEs must have the responsibility to understand and apply green accounting in their business operations. This is due to the important role of MSMEs as contributors to the country's economy, but also as producers of waste which can cause pollution and environmental damage. MSMEs have not implemented green accounting because there are no regulations governing this matter. The results show that the majority of MSMEs in Indonesia do not understand and applying green accounting to their financial reports. The majority of the obstacles are the low level of human resources and lack of socialization